2017
DOI: 10.1094/pdis-03-17-0410-re
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Penicillium sp. Causes Rot in Stored Sugar Beet Roots in Idaho

Abstract: Penicillium vulpinum along with a number of other fungi can lead to rot of stored sugar beet roots. However, Penicillium isolates associated with necrotic lesions on roots from a recent sugar beet storage study were determined to be different from P. vulpinum and other recognized Penicillium species. Phylogenies based on sequencing of the internal transcribed spacer (ITS)-5.8S, b-tubulin (BenA), and RNA polymerase II second largest subunit (RPB2) DNA regions indicate that these isolates are novel, but most clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Seven unique sequence types were found among the studied P . cellarum strains (F727 T , F759, F761, F769, F776, F785, F790) ( Strausbaugh and Dugan, 2017 , Strausbaugh, 2018 ). Those BenA , CaM and RPB2 sequences were re-analysed and compared with a set of nine P .…”
Section: Resultsmentioning
confidence: 99%
“…Seven unique sequence types were found among the studied P . cellarum strains (F727 T , F759, F761, F769, F776, F785, F790) ( Strausbaugh and Dugan, 2017 , Strausbaugh, 2018 ). Those BenA , CaM and RPB2 sequences were re-analysed and compared with a set of nine P .…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the optimal growth temperature of Diaporthe sp. is 22°C ( Strausbaugh and Dugan, 2017 ), and that of Cytospora hadianensis is 19.8°C ( Zhou et al., 2020 ). Helton and Konicek (1962) isolated six Cytospora species and indicated that the optimum pH is approximately 4.5, with a temperature of 20–35°C.…”
Section: Discussionmentioning
confidence: 99%
“…Recently a Penicillium‐like Talaromyces sp. has been reported to cause sucrose loss in sugar beet piles (Strausbaugh & Dugan, 2017; Strausbaugh, 2018). In this present study, the pathogenicity of Talaromyces pinophilus has been demonstrated in sugar beet.…”
Section: Figurementioning
confidence: 99%